A high-throughput sequencing approach identifies immunotherapeutic targets for bacterial meningitis in neonatesResearch in context - Stéphanie Pons; Eric Frapy; Youssouf Sereme; Charlotte Gaultier; François Lebreton; Andrea Kropec; Olga Danilchanka; Laura Schlemmer; Cécile Schrimpf; Margaux Allain; François Angoulvant; Hervé Lecuyer; et al. (EBioMedicine, 2023)
Summary: Background: Worldwide, Escherichia coli is the leading cause of neonatal Gram-negative bacterial meningitis, but full understanding of the pathogenesis of this disease is not yet achieved. Moreover, to date, no vaccine is available against bacterial neonatal meningitis. Methods: Here, we used Transposon Sequencing of saturated banks of mutants (TnSeq) to evaluate E. coli K1 genetic fitness in murine neonatal meningitis. We identified E. coli K1 genes encoding for factors important for systemic dissemination and brain infection, and focused on products with a likely outer-membrane or extra-cellular localization, as these are potential vaccine candidates. We used in vitro and in vivo models to study the efficacy of active and passive immunization. Results: We selected for further study the conserved surface polysaccharide Poly-β-(1-6)-N-Acetyl Glucosamine (PNAG), as a strong candidate for vaccine development. We found that PNAG was a virulence factor in our animal model. We showed that both passive and active immunization successfully prevented and/or treated meningitis caused by E. coli K1 in neonatal mice. We found an excellent opsonophagocytic killing activity of the antibodies to PNAG and in vitro these antibodies were also able to decrease binding, invasion and crossing of E. coli K1 through two blood brain barrier cell lines. Finally, to reinforce the potential of PNAG as a vaccine candidate in bacterial neonatal meningitis, we demonstrated that Group B Streptococcus, the main cause of neonatal meningitis in developed countries, also produced PNAG and that antibodies to PNAG could protect in vitro and in vivo against this major neonatal pathogen. Interpretation: Altogether, these results indicate the utility of a high-throughput DNA sequencing method to identify potential immunotherapy targets for a pathogen, including in this study a potential broad-spectrum target for prevention of neonatal bacterial infections. Fundings: ANR Seq-N-Vaq, Charles Hood Foundation, Hearst Foundation, and Groupe Pasteur Mutualité.